2014
DOI: 10.1111/cobi.12244
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Two Lion Conservation Programs in Maasailand, Kenya

Abstract: Lion (Panthera leo) populations are in decline throughout most of Africa. The problem is particularly acute in southern Kenya, where Maasai pastoralists have been spearing and poisoning lions at a rate that will ensure near term local extinction. We investigated 2 approaches for improving local tolerance of lions: compensation payments for livestock lost to predators and Lion Guardians, which draws on local cultural values and knowledge to mitigate livestock-carnivore conflict and monitor carnivores. To gauge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 34 publications
(61 reference statements)
4
164
0
8
Order By: Relevance
“…The African lion (Panthera leo) exemplifies the challenges of carnivore conservation: widespread habitat loss (4), extensive prey base depletion (5-7), indiscriminate retaliatory or preemptive killing to protect humans and their livestock (8)(9)(10), poorly regulated sport hunting (11)(12)(13)(14)(15)(16)(17)(18), and demand for traditional African and Chinese medicines (19). Although lions are relatively well-studied compared with most large felids, regional-scale population estimates remain scant across much of its range (20), and population surveys are generally repeated at irregular intervals because of the inherent difficulty of counting lions (21,22) and shortage of funds for systematic surveys.…”
mentioning
confidence: 99%
“…The African lion (Panthera leo) exemplifies the challenges of carnivore conservation: widespread habitat loss (4), extensive prey base depletion (5-7), indiscriminate retaliatory or preemptive killing to protect humans and their livestock (8)(9)(10), poorly regulated sport hunting (11)(12)(13)(14)(15)(16)(17)(18), and demand for traditional African and Chinese medicines (19). Although lions are relatively well-studied compared with most large felids, regional-scale population estimates remain scant across much of its range (20), and population surveys are generally repeated at irregular intervals because of the inherent difficulty of counting lions (21,22) and shortage of funds for systematic surveys.…”
mentioning
confidence: 99%
“…Indeed, this research has shown that despite there being common ground between stakeholders on what actions to take to improve coexistence, there were still a number of participants who did not agree with the consensus. Unless they also feel that their views are addressed, they may rebel against a mitigation scheme, which could have serious consequences on the future of carnivore conservation (Hazzah et al, 2014;Turnbull, Cain, & Roemer, 2013). It may well be that lethal control is still included as part of a conflict mitigation scheme, particularly for small stock farmers managing non-threatened but potentially highlydamaging species such as jackals and caracals.…”
Section: Discussionmentioning
confidence: 99%
“…In communities that were meant to receive compensation but where payment was not received, locals became frustrated at the scheme. This could result in widespread poaching of predators if communities do not receive what is perceived to be adequate reimbursement for damage to property (Hazzah et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations